Induction of chemokine (C‐C motif) ligand 5 by Epstein–Barr virus infection enhances tumor angiogenesis in nasopharyngeal carcinoma. Issue 5 (28th April 2018) - Ma, Wenlong; Feng, Lin; Zhang, Shanshan; Zhang, Haojiong; Zhang, Xiao; Qi, Xuekang; Zhang, Yuchen; Feng, Qisheng; Xiang, Tong; Zeng, Yi‐Xin
Abstract : Nasopharyngeal carcinoma (NPC) is etiologically associated with Epstein–Barr virus (EBV) infection and is known to be highly vascularized. Previous studies have suggested that EBV oncoproteins contribute to NPC angiogenesis. However, the regulatory network of EBV in angiogenesis still remains elusive. Herein, we reveal a novel mechanism of EBV‐induced angiogenesis in NPC. First, we showed that EBV‐infected NPC cell lines generated larger tumors with more microvessels in mouse xenograft models. Subsequent proteomic analysis revealed that EBV infection increased the expression of a series of angiogenic factors, including chemokine (C‐C motif) ligand 5 (CCL5). We then proved that CCL5 was a target of EBV in inducing tumor angiogenesis and growth. Further investigation through transcriptome analysis indicated that the pro‐angiogenic function of CCL5 might be mediated by the PI3K/AKT pathway. Furthermore, we confirmed that activation of the PI3K/AKT and hypoxia‐inducible factor‐1α pathways was essential for CCL5‐promoted angiogenesis. Finally, the immunohistochemical analysis of human NPC specimens also showed that CCL5 was correlated with angiogenesis. Taken together, our study identifies CCL5 as a key EBV‐regulated molecular driver that promotes NPC angiogenesis, suggesting it as a potential therapeutic target. Abstract : Our study revealed that EBV infection promotes the production of CCL5, which increases VEGF expression and NPC angiogenesis by interacting with the PI3K/AKT and HIF‐1α pathways.